World-Level Analysis in Top Level Football Analysis and Simulation of Football Specific Group Tactics by Means of Adaptive Neural Networks - Daniel, Memmert; Jürgen, Bischof; Stefan, Endler; Andreas, Grunz; Markus, Schmid; Andrea, Schmidt; Jürgen, Perl (IntechOpen, 2011)
None